Vaccine Protection of Mice With Primary Immunodeficiencies Against Disseminated Coccidioidomycosis - Powell, Daniel A.; Hsu, Amy P.; Butkiewicz, Christine D.; Trinh, Hien T.; Frelinger, Jeffrey A.; Holland, Steven M.; Galgiani, John N.; Shubitz, Lisa F. (Frontiers in Cellular and Infection Microbiology, 2022)
Disseminated coccidioidomycosis (DCM), often a severe and refractory disease leading to poor outcomes, is a risk for people with certain primary immunodeficiencies (PID). Several DCM-associated PID (STAT4, STAT3, IFNγ, and Dectin-1) are modeled in mice. To determine if vaccination could provide these mice protection, mice with mutations in Stat4, Stat3, Ifngr1, Clec7a (Dectin-1), and Rag-1 (T- and B-cell deficient) knockout (KO) mice were vaccinated with the live, avirulent, Δcps1 and subsequently challenged intranasally with pathogenic Coccidioides posadasii Silveira strain. Two weeks post-infection, vaccinated mice of all strains except Rag-1 KO had significantly reduced lung and spleen fungal burdens (p<0.05) compared to unvaccinated control mice. Splenic dissemination was prevented in most mice of vaccinated immunodeficient while all unvaccinated B6 mice and the Rag-1 KO mice displayed disseminated disease. The mitigation of DCM by Δcps1 vaccination in these mice suggests that it could also benefit humans with immunogenetic risks of severe disease.